How responsive are housing markets in the OECD? Regional level estimates - Bétin, Manuel (OECD Publishing, 2019)
Making housing more affordable ranks high on the policy agenda across the world. One way to achieve affordable housing is to ensure sufficiently elastic supply of the housing stock in response to demand shocks. This paper aims at disentangling policy from non-policy drivers in explaining cross-regional differences in housing supply elasticities. It uses GIS data to account for the presence of natural and man-made obstacles to residential construction in functional urban areas across the 12 OECD countries that provide sufficiently long time series for regional house prices. The results suggest that the presence of water, steep land, parks and high-density urban areas all restrict the supply of housing. However, there remain very large differences in supply elasticities across countries, which corroborates the finding from national analysis that policies have a strong influence
Keywords: Economics